Anemia Prevention Education for Adolescent Girls through Consumption of Iron-Rich Foods at Muhammadiyah 5 High School, Lubuk Pakam - Salmi Angraini; Dian Novita; Wira Maria Ginting (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2026)
Anemia remains one of the most common nutritional problems among adolescent girls, primarily caused by inadequate iron intake and increased iron requirements during growth. Limited knowledge regarding iron-rich foods can increase the risk of anemia. This community service activity aimed to improve adolescent girls' knowledge about anemia prevention through the consumption of iron-rich foods. The program was conducted in May 2026 at SMA Muhammadiyah 5 Lubuk Pakam, North Sumatra, involving 30 female students of grade XII. The educational intervention consisted of interactive lectures, discussions, and simulations using food cards based on the Indonesian Food Composition Table (TKPI) to identify iron-rich food sources. Evaluation was carried out using pre-test and post-test assessments. The results showed a significant improvement in students’ knowledge after the educational program. Before the intervention, 36.7% of participants had good knowledge, 43.3% had moderate knowledge, and 20.0% had poor knowledge. After the intervention, the proportion of students with good knowledge increased to 86.7%, while 13.3% remained in the moderate category and no students were classified as having poor knowledge. Participants also demonstrated high enthusiasm during discussions and simulations and were able to identify iron-rich foods and strategies to enhance iron absorption. These findings indicate that nutrition education on the consumption of iron-rich foods is effective in improving knowledge and understanding among adolescent girls as an effort to prevent anemia.